2021
DOI: 10.1053/j.jvca.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Angiotensin II Is Associated With Rapid Blood Pressure Response and Vasopressor Sparing in Patients With Vasoplegia After Cardiac Surgery: A Post-Hoc Analysis of Angiotensin II for the Treatment of High-Output Shock (ATHOS-3) Study

Abstract: Objective: The present study investigated outcomes in patients with vasoplegia after cardiac surgery treated with angiotensin II plus standard-ofcare vasopressors. Vasoplegia is a common complication in cardiac surgery with cardiopulmonary bypass and is associated with significant morbidity and mortality. Approximately 250,000 cardiac surgeries with cardiopulmonary bypass are performed in the United States annually, with vasoplegia occurring in 20%to-27% of patients. Design: Post-hoc analysis of the Angiotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Although relatively few patients in the ATHOS-3 trial had undergone cardiac surgery (4.7%; 16 of 344), this was examined in detail in a post hoc analysis. 6 In that report, 89% of the cardiac surgery cohort reached the target mean arterial pressure. In addition, the overall ATHOS-3 Ang-II cohort had a higher rate of venous thromboembolism (VTE) than the standard of care group (13% vs 5%) but a similar rate of clinically significant VTEs (2% vs 0%).…”
Section: Subhasis Chatterjee MDmentioning
confidence: 93%
“…Although relatively few patients in the ATHOS-3 trial had undergone cardiac surgery (4.7%; 16 of 344), this was examined in detail in a post hoc analysis. 6 In that report, 89% of the cardiac surgery cohort reached the target mean arterial pressure. In addition, the overall ATHOS-3 Ang-II cohort had a higher rate of venous thromboembolism (VTE) than the standard of care group (13% vs 5%) but a similar rate of clinically significant VTEs (2% vs 0%).…”
Section: Subhasis Chatterjee MDmentioning
confidence: 93%
“…5 This vasopressor-sparing effect may minimize the ischemic risk by supporting a more balanced restoration of vascular tome. [7][8][9] Although this report expands the therapeutic armamentarium for vasoplegia, it also highlights some important caveats with this vasopressor. [5][6][7][8][9] The first caveat is that we know very little about adverse events associated with angiotensin II, owing to the limited evidence base.…”
mentioning
confidence: 91%
“…We would like to congratulate the authors of their post-hoc analysis of Angiotensin II (ANG-II) for the treatment of vasoplegia in patients following cardiac surgery. 1 The study found that patients with vasoplegia after cardiac surgery with cardiopulmonary bypass rapidly responded to ANG-II with swift blood pressure response and rapid down titration of standard of care vasopressors with no reported thrombosis. 1 Early recognition and treatment of vasoplegia improves survival and reduces risks of major adverse events.…”
mentioning
confidence: 95%
“…1 The study found that patients with vasoplegia after cardiac surgery with cardiopulmonary bypass rapidly responded to ANG-II with swift blood pressure response and rapid down titration of standard of care vasopressors with no reported thrombosis. 1 Early recognition and treatment of vasoplegia improves survival and reduces risks of major adverse events. 2 However, in patients with heart failure and severe vasoplegia, treatment with ANG-II is not widely utilized despite the data demonstrating the efficacy of the drug.…”
mentioning
confidence: 95%
See 1 more Smart Citation